Perceived social support in the social distancing era: the association between circles of potential support and COVID-19 reactive psychopathology. Issue 1 (2nd January 2022) - Ferber, Sari Goldstein; Weller, Aron; Maor, Rotem; Feldman, Yuval; Harel-Fisch, Yossi; Mikulincer, Mario
ABSTRACT: Background and Objectives: Stressors related to the COVID-19 pandemic are risk factors for psychopathology, but psychosocial protective factors might play a crucial role in buffering the pathogenic effects of the outbreak. Design: In the current study, we examined the association of inner resources and potential external sources of support for coping with the pandemic and related lockdowns to mental health during the pandemic, while controlling for sociodemographic variables as covariates. Methods: We tested the model in a probability-based internet survey of a representative sample of the Israeli adult population ( N = 812) conducted during the COVID-19 pandemic. Results: Perceived support in close relationships was negatively associated with the intensity of depression, anxiety, obsessive-compulsive disorder (OCD) and post-traumatic stress disorder (PTSD). Larger rings of potential support such as perceived belongingness to a community and trust in government were also negatively related to anxiety and depression but were positively associated with the intensity of OCD and PTSD. Conclusions: Findings support the "tend and befriend" theory in the social distancing era and highlight the importance of keeping personal relationships alive when facing a mass trauma.